SEXUALITY AND SEXUAL DIVERSITY IN THE FORMATION IN PSYCHOLOGY - Maia, Ana Cláudia Bortolozzi (2018)
This article presents a theoretical discussion about the theme of sexuality and diversity in the area of formation in Psychology, based on three fundamental issues: 1) Sexuality as a historical construction, 2) Psychology facing the normativity and the prejudice and The Professional Ethics Code and 3) The formation in Psychology and the sexual diversity. It is concluded that, in spite of the recognition of the right to sexuality with a multiple and diverse expression, many normative and discriminative conceptions still predominate in the common sense and also in the practice of psychologists, so there is the need to invest in the formation of those professionals that should, as a principle, respect and defend the right to a plural sexuality.